Oral hygiene and periodontal status among children and adolescents residing at an orphanage in Udaipur city, India. (Nigerian Dental Journal, 2008)
Objective: To assess the oral hygiene and periodontal status; to analyze the influence of age, education, institutionalization and oral hygiene practices on oral hygiene status among children residing at an orphanage in Udaipur city, India.Method: The total sample comprised of 256 male children and adolescents between the ages 5 to 16 years residing at an orphanage in Udaipur city, India. Clinical examination included assessment of oral hygiene and periodontal status using OHI-S (Oral Hygiene Index Simplified) and CPI (Community Periodontal Index) respectively.Result: The overall prevalence of periodontal disease was 89.1%. Debris was the dominant expression of oral hygiene index in all the age groups. Mean OHI- S along with mean scores of its components increased with age. The proportions of subjects with gingival bleeding decreased significantly with age and those with calculus increased steadily with age. The overall mean number of healthy sextants was 3.5 and this decreased with age. Bivariate and multivariate analysis revealed that age, education, years of institutionalization, tooth cleaning frequency and substance used to clean teeth was significantly related to debris,calculus and oral hygiene status.Conclusion: Oral hygiene status was generally good, with barely 12.9% subjects exhibiting poor oral cleanliness and the overall prevalence of periodontal disease was 89.1%. Age, level of education, years of institutionalization and oral hygiene practices were significantly related to oral hygiene status.